PARENTS’ EXPECTATIONS OF THE TEACHING AND LEARNING ISLAMIC EDUCATION - Hasanah, Nur (Jurnal Pendidikan Islam, 2016)
The focuses of this research is on parentsâ€™ expectation of the teaching and learning Islamic Education among students of SDLB N Ungaran. The subject is Islamic Education teachers and the parents of students in SDLB N Ungaran. The methods of data collections are observation, interview and documentation. The technique of data analysis is inductive analysis. The result shows that the teaching and learning Islamic Education among students of SDLB N Ungaran is generally almost the same with the teaching and learning Islamic Education among students of general school. The difference is only in the psychological aspect. The majority of parentsâ€™ expectation of the teaching and learning Islamic Education is the same: in order the students can understand and apply the subject of Islamic Education in their everyday life so that they can become the righteous children. The factors that support the teaching and learning Islamic Education among students of SDLB N Ungaran are the Islamic Education teachersâ€™ patients and meticulous, cooperation between parents, teachers and the school, the extracurricular subjects which are suitable with the studentsâ€™ talent and ability, and teachersâ€™ creativity in teaching and learning. The factors that hinder the teaching and learning Islamic Education are inefficient and ineffective time (not suitable with the students with physical disabilities), using the same curriculum with the curriculum in the general school, the low quality teachers, and the lack of teaching and learning facilities. Â